1993
DOI: 10.1152/ajpregu.1993.264.5.r917
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin type 2 receptors mediate depressor phase of biphasic pressure response to angiotensin

Abstract: Angiotensin (ANG) can produce a biphasic arterial pressure response, i.e., an increase followed by a decrease. Because ANG type 1 (AT1) receptors mediate the pressor response to ANG, we hypothesized that the opposing depressor action is mediated by the ANG type 2 (AT2) receptors. In thiobutabarbital (Inactin)-anesthetized rats bolus injections of angiotensin III (ANG III; 100, 300, and 1,000 ng/kg iv) produced peak increases in MAP at 20 s of 13.4 +/- 1.4, 20.1 +/- 2, and 27.5 +/- 2.8 mmHg and maximum decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
4

Year Published

1993
1993
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 0 publications
5
71
4
Order By: Relevance
“…The vasopressor response was mediated by angiotensin AT 1 while the vasodepressor response was related to angiotensin AT 2 receptors. 8 Furthermore, mice with targeted deletion of the AT 2 receptor is associated with vascular and renal hypersensitivity to angiotensin II, including sustained antidiuresis and hypertension. 39 Thus, the existence of an equilibrium between pressor AT 1 and depressor AT 2 receptor should be proposed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The vasopressor response was mediated by angiotensin AT 1 while the vasodepressor response was related to angiotensin AT 2 receptors. 8 Furthermore, mice with targeted deletion of the AT 2 receptor is associated with vascular and renal hypersensitivity to angiotensin II, including sustained antidiuresis and hypertension. 39 Thus, the existence of an equilibrium between pressor AT 1 and depressor AT 2 receptor should be proposed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that angiotensin II can elicit a biphasic arterial pressure response in rabbits 7 and rats. 8 Furthermore, endothelium-dependent relaxations induced by angiotensin II have been reported in a variety of experimental preparations such as the fowl aorta 9 and canine renal and cerebral arteries. 10 The heterogeneity of the response to angiotensin II may be related to modulatory effects of the vascular endothelium or stimulation of different angiotensin II receptor subtypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is blocked by PD 123177. 98 Also, co-infusion of rats with Ang II and PD 123199 results in an enhanced blood pressure response as compared to rats infused with Ang II alone. 99 Although the AT 2 receptor seems to be involved in growth and differentiation, lack of a functional receptor still allows for development of an organism as illustrated by the establishment of AT 2 knockout mice strains.…”
Section: At 2 Receptor and Signal Transductionmentioning
confidence: 99%
“…This effect is blocked by PD 123177. 88 Also, coinfusion of rats with Ang II and PD 123199 results in an enhanced blood pressure response, as compared to rats infused with Ang II alone. 89 Although the AT 2 receptor seems to be involved in growth and differentiation, lack of a functional receptor still allows for development of an organism, as illustrated by the establishment of AT 2 knockout mice strains.…”
Section: Development Of Ang Ii-receptor Binding Substancesmentioning
confidence: 99%